2022
DOI: 10.1039/d2ta06208a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic weak coordination bonding of chlorocarbons enhances the catalytic performance of a metal–organic framework material

Abstract: Solvents with weak coordination bonding (e.g., TCM and DCM) confined in the nanopores of a metal–organic framework undergo dynamic coordination exchange with stronger Lewis-basic solvents (e.g., H2O), and they lead to enhanced catalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…During the reaction, a high conversion is maintained in the initial stages of the reaction (Sc( iii ) sites are continuously available), then the conversion decreases (the Sc( iii ) sites become less available or are generated at a lower rate), before recovering to a similar (slightly higher) value to that observed in the initial stages of the reaction (increased in conversion). Recently, Jeong et al , 16 reported that having permanent access to the LAS is essential for higher catalytic activity, which in our system is challenging, thereby corroborating the hypothesis that non-permanent access to the active sites is responsible for the observed behavior on stream. Generally, conventional catalysts show a conversion equilibrium over time-on-stream when the steady state is reached.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…During the reaction, a high conversion is maintained in the initial stages of the reaction (Sc( iii ) sites are continuously available), then the conversion decreases (the Sc( iii ) sites become less available or are generated at a lower rate), before recovering to a similar (slightly higher) value to that observed in the initial stages of the reaction (increased in conversion). Recently, Jeong et al , 16 reported that having permanent access to the LAS is essential for higher catalytic activity, which in our system is challenging, thereby corroborating the hypothesis that non-permanent access to the active sites is responsible for the observed behavior on stream. Generally, conventional catalysts show a conversion equilibrium over time-on-stream when the steady state is reached.…”
supporting
confidence: 87%
“…15 For example, LAS at HKUST-1 was used for hydrogenation reaction. 16 MIL-101(Cr)-X (X: H, NO 2 , SO 3 H, Cl, CH 3 , and NH 2 ) act as catalysts for epoxide ring opening, benzaldehyde acetalization, and coupling reaction by three Lewis acid-catalyzed reactions. 17 Furthermore, different MOFs have been applied in a varied range of catalytic reactions, such as MIL-100 for the intermolecular carbonyl reaction, 18 Cu-BTC for the cyanosilylation reaction, 19 and UiO-66 for the CO 2 cycloaddition reaction.…”
mentioning
confidence: 99%
“…Encouraged by these results, we prepared integrated Ni@NH 2 -MOFs with preinstalled Ni center(s) by a simple impregnation method (see the preparation details and structural characterizations in the Method section and Supporting Information, Figures S1, S3b, and S4–S5). The Ni level in these integrated catalysts ranged from 0.146 to 1.65 wt %, corresponding to Ni:Zr­(Ti) ratios of 0.028 (NH 2 -UiO-66), 0.01 ((NH 2 ) 2 -UiO-67), and 0.057 (NH 2 -MIL-125), and cell occupancies of 16.7% (NH 2 -UiO-66), 6% ((NH 2 ) 2 -UiO-67), and 45.6% (NH 2 -MIL-125), respectively (Table S2). Gratifyingly, the integrated Ni@NH 2 -UiO-MOFs exhibited substantially enhanced C–O coupling yields and selectivity ( Figure and Table S1), presumably due to more active Ni sites formed in the preassembled samples.…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the integrated MOF with implant Ni centers, the corresponding MOF was first activated at 120 °C under vacuum for 5 h. Then, the activated MOF (100 mg) was suspended in 10 mL of methanol and sonicated for 30 min, followed by addition of 10 mL NiCl 2 ·6H 2 O methanol solution (0.16 M). The mixture was stirred in the dark for 24 h for Ni coordination.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few decades, organic–inorganic hybrid materials (OIHMs) have gained significant attention owing to their structural versatility, ranging from zero- to higher-dimensional structures, through the use of metal nodes and organic frameworks. OIHMs offer the potential to combine the advantages of organic and inorganic components for a variety of material applications, making them useful in fields such as catalysts, energy applications, sensors, and optics. ,, Among many, Mn­(II) has been actively investigated due to its luminescence properties being highly dependent on the coordination environment. Four-coordinate Mn­(II) typically exhibits green emission, while six-coordinate Mn­(II) shows red emission. Low-dimensional OIHMs with manganese sources have been studied in the field of photoluminescence due to their high quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%